Aortic valve calcification and endomyocardial fibrosis determine adverse outcomes following transcatheter aortic valve replacement. (4th February 2022) - Evertz, R; Hub, S; Beuthner, B; Backhaus, S; Lange, T; Topci, R; Toischer, K; Kowallick, J; Puls, M; Zeisberg, E; Hasenfuss, G; Schuster, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Aims: There is evidence to suggest that subtype of aortic stenosis (AS), degree of myocardial fibrosis (MF) and level of aortic valve calcification (AVC) are associated with adverse cardiac outcome in AS. Since little is known about their respective contribution, we sought to investigate their relative importance and interplay as well as association with adverse cardiac events. Methods: 100 consecutive patients with severe AS and indication for transfemoral transcatheter aortic valve replacement (TAVR) were prospectively enrolled between January 2017 and October 2018. Patients underwent transthoracic echocardiography, multi detector computed tomography (MDCT) and left ventricular endomyocardial biopsy at the time of TAVR. Results: The final study cohort consisted of 92 patients with completed study protocol comprising of 39 (42.4 %) normal ejection fraction high gradient (NEFHG), 13 (14.1 %) low EF high gradient (LEFHG), 25 (27.2 %) low EF (flow) low gradient (LEFLG) and 15 (16.3 %) paradoxical low flow low gradient (PLFLG) AS. The high gradient phenotypes (NEFHG and LEFHG) showed the largest amount of AVC (807 ± 421; 813 ± 281 mm³ respectively) as compared to the low gradient phenotypes (LEFLG and PLFLG; 503 ± 326; 555 ± 594 mm³ respectively, p < 0.05). Conversely, MF was most prevalent in low output phenotypes (LEFLG > LEFHG > PLFLG > HEFHG, p < 0.05). This was paralleled by larger cardiovascular mortality within 600 days post TAVR (LEFLG n = 7 > PLFLG n = 4 > LEFHG n = 2 > NEFHG n = 1). In Patients with high MF burden a higher AVC was associated with a lower mortality (p = 0.045, HR = 0.261, 95%CI 0.07-0.97). Within LEFLG AS, patients with larger AVC (>476.8 mm³) had larger MF (40.2%) and higher cardiovascular mortality (n = 5) as compared to patients with lower AVC (£476.8 mm³, 17.1% MF, p = 0.027, cardiovascular mortality n = 2). Conclusion: MF is associated with adverse cardiovascular outcome following TAVR which is most prevalent in low ejection fraction situations. In the presence of large MF burden patients with large AVC have better outcome following TAVR. Conversely worse outcome in large MF and relatively little AVC may be explained by a relative prominence of an underlying cardiomyopathy while better survival rates in large AVC patients may indicate severe AS associated pressure overload relief and subsequently improved survival following TAVR.